2007
DOI: 10.1007/s10653-007-9096-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of As(V) adsorption onto activated sludge by methylation treatment

Abstract: Biosorption properties of arsenate [As(V)] onto activated sludge were investigated in batch systems. The adsorption of As(V) onto sludge increased from 23 to 266 microg/g dry weight through the methylation of the activated sludge. This increase resulted from neutralization of carboxylic groups via the methylation process. The pH effect of As(V) uptake was also investigated and As(V) adsorption by methylated sludge decreased significantly at high pH (pH > 11) due to competition between As(V) and OH(-) ions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Wave numbers of the peaks corresponding with absorption bands and their characteristic shown in Table 2 were used during analyzing environmental sample’s spectra. In case of developed spectra library, other publications concerning FT-IR analysis, using similar methodology, obtained roughly the same results, and peaks were observed in very similar regions (Quilès et al 2010 ; Gulnaz et al 2006 ; Wharfe et al 2010 ; Cheftez et al 2006 ; Amir et al 2010 ; Kang et al 2007 ; Guibaud et al 2003 ).…”
Section: Resultssupporting
confidence: 68%
“…Wave numbers of the peaks corresponding with absorption bands and their characteristic shown in Table 2 were used during analyzing environmental sample’s spectra. In case of developed spectra library, other publications concerning FT-IR analysis, using similar methodology, obtained roughly the same results, and peaks were observed in very similar regions (Quilès et al 2010 ; Gulnaz et al 2006 ; Wharfe et al 2010 ; Cheftez et al 2006 ; Amir et al 2010 ; Kang et al 2007 ; Guibaud et al 2003 ).…”
Section: Resultssupporting
confidence: 68%
“…There was little difference in As ads (accounting for 23.5–27.7% of the total arsenic) among all assays whether the sulfate or voltage was applied or not. Interactions between arsenic and surface functional groups of sludge are considered as the primary mechanisms for arsenic adsorption . Our previous study found that the adsorption of arsenic was negatively impacted by increasing pH, ionic strength, and phosphate ions .…”
Section: Resultsmentioning
confidence: 99%
“…3) with 500 mM of arsenate. Adsorption of arsenate at high pH could be due to an increased negative charge on the cell surface which favored the electrochemical attraction and increased adsorption of the metal (Kang et al 2007). …”
Section: Resultsmentioning
confidence: 99%